Impacts of climate and land‐cover changes on water resources in a humid subtropical watershed: a case study from East Texas, USA. (22nd July 2014) - Heo, Joonghyeok; Yu, Jaehyung; Giardino, John R.; Cho, Huidae
Abstract This study investigates the response of water resources regarding the climate and land‐cover changes in a humid subtropical watershed during the period 1970–2009. A 0.7°C increase in temperature and a 16.3% increase in precipitation were observed. Temperature had a lower increase trend, and precipitation showed definite increasing trend compared to previous studies. The main trend of land‐cover change was conversion of vegetation and barren lands to developed and crop lands affected by human intervention, and forest and grass to bush/shrub which considered to be caused by natural climate system. Hydrologic responses to climate and land‐cover changes resulted in increases of surface run‐off (15.0%), soil water content (2.7%), evapotranspiration (20.1%) and a decrease in groundwater discharge (9.2%). We found that surface run‐off is relatively stable with precipitation, whereas groundwater discharge and soil water content are sensitive to changes in land cover, especially land cover brought about by human intervention.